Honor ebook - Umrigar, Thrity (2022)
THE JANUARY 2022 REESE'S BOOK CLUB PICK “In the way  A Thousand Splendid Suns  told of Afghanistan’s women, Thrity Umrigar tells a story of India with the intimacy of one who knows the many facets of a land both modern and ancient, awash in contradictions.” —Lisa Wingate, #1 New York Times bestselling author of  Before We Were Yours   In this riveting and immersive novel, bestselling author Thrity Umrigar tells the story of two couples and the sometimes dangerous and heartbreaking challenges of love across a cultural divide.   Indian American journalist Smita has returned to India to cover a story, but reluctantly: long ago she and her family left the country with no intention of ever coming back. As she follows the case of Meena—a Hindu woman attacked by members of her own village and her own family for marrying a Muslim man—Smita comes face to face with a society where tradition carries more weight than one’s own heart, and a story that threatens to unearth the painful secrets of Smita’s own past. While Meena’s fate hangs in the balance, Smita tries in every way she can to right the scales. She also finds herself increasingly drawn to Mohan, an Indian man she meets while on assignment. But the dual love stories of Honor are as different as the cultures of Meena and Smita themselves: Smita realizes she has the freedom to enter into a casual affair, knowing she can decide later how much it means to her. In this tender and evocative novel about love, hope, familial devotion, betrayal, and sacrifice, Thrity Umrigar shows us two courageous women trying to navigate how to be true to their homelands and themselves at the same time.